Endoscopic Treatment of Intussusception due to Intestinal Tuberculosis - Dooyoup Kim; Hyundo Jung; Mindae Kim; Jaehyung Lee; Sukhun Kim; Dongku Kang; Jiha Kim; Ilseon Lee (Korean Society of Gastrointestinal Endoscopy, 2017)
Traditionally, adult intussusception has required a bowel resection because of the malignancy risk. A patient with anorexia, weight loss, and abdominal pain visited our clinic. A physical exam and imaging study revealed no acute peritoneal signs. A colonoscopy for biopsy and bowel reduction was attempted. The tissue sample was consistent with intestinal tuberculosis. We report intestinal tuberculosis complicating intussusception which was treated without surgical intervention.